Trace element signatures of sphalerite in the Sichuan Daliangzi Ge-rich Pb-Zn deposit and its implications for deep ore prospecting - Li, Lingjie; Han, Runsheng; Zhang, Yan; Wu, Jianbiao; Feng, Zhixing (Frontiers in Earth Science, 2022)
The Daliangzi Pb-Zn deposit is one of the typical Ge-rich Pb-Zn deposits in Sichuan-Yunnan-Guizhou Pb-Zn polymetallic metallogenic triangle area (SYGT), with its Pb, Zn, and Cd reserves reaching the scale of a large-sized deposit and its Ge reserve reaching that of a medium-sized deposit. Based on LA-ICP-MS in-situ analysis in combination with element mapping, this paper reveals the occurrence state of trace elements and ore-forming temperature of sphalerite in ores. The study shows that the sphalerite in the deposit is characterized by rich Cd, Ge, and Ga, relatively rich Fe, very variable Cu and Pb contents, and poor Mn, In, and Sn, where major elements such as Cd, Mn, Fe, and Pb occur in sphalerite in the form of isomorphism or locally in the form of microinclusions in galena; good correlation between Cu(Ag) and Ge and that between (Cu+Ag) and (Ga+As+Sb) suggest that the substitution relationship with Zn is nCu2++Ge2+↔(n+1)Zn2+ or n(Cu, Ag)2++Ge2+↔(n+1)Zn2+ and (Cu+Ag)1++(Ga+As+Sb)3+↔2Zn2+, and chalcopyrite and Ge, Gu, and Ga-rich microinclusions exist locally; the contents of Ge, Cd, Cu, Pb, Fe, Mn, and other elements in brown yellow sphalerite are higher than those in light yellow sphalerite while Ga and In are relatively more enriched in the latter. The estimation by GGIMFis geothermometer and the trace element signature of the sphalerite indicate that the temperature of the deposit is low-moderate: the formation temperature of the sphalerite at stage II is 86-213℃ (136℃ in average) ~ 106-238℃ (171℃ in average) and that at stage III is 88-105℃ (96℃ in average) ~ 134-147℃ (140℃ in average), demonstrating that the precipitation mechanism of ore-forming elements is the drop in fluid temperature . Based on this, an ore-forming model of the deposit has been established, and it is believed that the ore district has a potential for deep prospecting of Gu, Pb, Zn, and other metal resource.